Utility of kindergarten teacher judgments in identifying early learning problems. - Taylor HG; Anselmo M; Foreman AL; Schatschneider C; Angelopoulos J (Journal of Learning Disabilities)
Most existing research on early identification of learning difficulties has examined the validity of methods for predicting future academic problems. The present study focused instead on the sensitivity of kindergarten teachers to learning problems in their students and on the continuity of teacher-identified problems over time. To identify early learning problems, kindergarten teachers in a suburban school district rated student progress toward six academic objectives as satisfactory or unsatisfactory. Twenty percent of the district's 303 kindergarten children received unsatisfactory ratings in at least one area. Thirty-eight of these children (identified group) were matched to 34 children with satisfactory ratings in all areas (nonidentiffed group). Results of testing conducted during kindergarten revealed poorer academic achievement in identified children than in nonidentified children. Children from the identified group also performed more poorly than children from the nonidentified group on tests of phonological processing and working memory/ executive function and were rated by teachers as having more behavior and attention problems and lower social competence. Follow-up of the sample to first grade documented continued learning problems in the identified group. These findings support the use of teacher judgements in early detection of learning problems and argue against reliance on discrepancy criteria.